Exploring the Impact of Songs in EFL Teaching Across Age Groups: Perspectives from Vietnamese EFL Lecturers - Pham, Trut Thuy; Le, Thanh Thao (Journal of Innovation and Research in Primary Education, 2024)
This study investigates the effectiveness of using songs in English as a Foreign Language (EFL) teaching from the perspectives of Vietnamese EFL lecturers, focusing on identifying the most beneficial age group among young learners, teenagers, and adult learners. Employing a qualitative research design, the study conducted semi-structured interviews with nine EFL teachers from two educational institutions in Vietnam, representing a range of experience levels from novice to near-end career. The data were analyzed using thematic analysis, guided by Constructivist and Socio-cultural theories of learning. The findings revealed that the application and perceived effectiveness of songs varied significantly across different age groups and teacher experience levels. Songs were universally recognized as beneficial in EFL teaching, but their implementation and impact differed, with novice teachers focusing on engagement, mid-career teachers on cultural and linguistic nuances, and near-end career teachers on a holistic language experience. The study found that songs are highly effective with young learners, need careful selection for teenagers, and should be thematically rich for adult learners. These insights have implications for EFL practitioners, curriculum designers, and policymakers, suggesting the need for tailored song-based activities and professional development for teachers.